The novel E. coli cell division protein, YtfB, plays a role in eukaryotic cell adhesion - Bottomley, Amy L. (2021)
Characterisation of protein function based solely on homology searches may overlook functions under specific environmental conditions, or the possibility of a protein having multiple roles. In this study we investigated the role of YtfB, a protein originally identified in a genome-wide screen to cause inhibition of cell division, and has demonstrated to localise to the Escherichia coli division site with some degree of glycan specificity. Interestingly, YtfB also shows homology to the virulence factor OapA from Haemophilus influenzae, which is important for adherence to epithelial cells, indicating the potential of additional function(s) for YtfB. Here we show that E. coli YtfB binds to N’acetylglucosamine and mannobiose glycans with high affinity. The loss of ytfB results in a reduction in the ability of the uropathogenic E. coli strain UTI89 to adhere to human kidney cells, but not to bladder cells, suggesting a specific role in the initial adherence stage of ascending urinary tract infections. Taken together, our results suggest a role for YtfB in adhesion to specific eukaryotic cells, which may be additional, or complementary, to its role in cell division. This study highlights the importance of understanding the possible multiple functions of proteins based on homology, which may be specific to different environmental conditions.